The Practice of Accommodating Students in American Higher Education Institutions - Holovatenko, Tetiana (Educological discourse, 2024)
The article explores the provision of accommodations in the process of learning academic courses in higher education institutions (hereinafter - HEIs) using a comparative approach. The relevance of the study is due to a number of contradictions between the growing demands of society to take into account the individual characteristics of students in the context of the war in Ukraine and the limitation of such accommodations in HEIs by didactic approaches; the strategy of individualization of the educational process defined at the legislative level and the lack of units in HEIs responsible for ensuring equal access to education for students; the need to study foreign experience in training students in HEIs and the state of development of the topic. The purpose of the study is to conduct a comprehensive analysis of the system of providing accommodations in the study of academic courses in US HEIs and to outline ways to implement the American experience in Ukraine. The research methodology is based on the qualitative comparative research methodology. The research data was obtained by analyzing empirical data collected from pedagogical observation, analysis, synthesis and generalization of data. The study sample included 11 US HEIs that accommodate students by provising Letters of Accommodation. The results of the study identify ways to implement such accommodations, describe the departments responsible for creating conditions for equal access to education and accommodation, define eligibility criteria, describe the procedure for obtaining accommodation for academic courses, and ways faculty implement the accommodation recommendation. It is found that the three main ways to implement accommodations are the introduction of universal design into the development of course materials and class activities, changes in the physical space of the classroom and classroom management, and the use of didactic ways to ensure accommodations. The prospects for implementing the American experience in Ukraine are the establishment of departments that would deal with issues of equal access to education and provide recommendations on accommodation for students; the introduction of screening and diagnostic procedures in higher education institutions in cooperation with relevant experts to determine the need for accommodation for students; and the introduction of universal design principles into the content of academic courses.